Penggunaan Strategi Bercerita pada Materi Sejarah Kebudayaan Islam di MTs Nurul Falah Sibiruang Koto Kampar Hulu - Asmardi, Asmardi; Pasaribu, Munawir (Fakultas Tarbiyah IAI Nasional Laa Rooiba, 2024)
This research aims to analyze the use of storytelling strategies in Islamic cultural history material at MTS Nurul Falah Sibiruang Koto Kampar Hulu. The research method used is qualitative research with students as research subjects. Data was collected through classroom observations, interviews with teachers, and document analysis. The research results show that the use of storytelling strategies in learning the history of Islamic culture can increase students' interest and involvement in the learning process. Students responded positively to the use of stories as a means of understanding the historical context and values ​​of Islamic culture. Apart from that, teachers also feel the positive impact of using this strategy, because it can increase student participation and involvement in learning. Overall, storytelling strategies can be an effective alternative in improving learning about the history of Islamic culture at MTS Nurul Falah Sibiruang Koto Kampar Hulu. This research makes an important contribution in strengthening innovative and interesting learning approaches for teachers and students in understanding and appreciating Islamic culture. The results of this research can be used as a reference by other educational institutions to enrich learning methods for the history of Islamic culture in order to achieve a deeper understanding and appreciation of Islamic and cultural values. Keywords: Storytelling strategy; history of Islam; MTs Nurul Falah Sibiruang Koto